Global Effects in Political Ideology-Case of Kosovo - Mexhuani, Burim (European Journal of Multidisciplinary Studies, 2017)
: The paper examines the global effects on political ideologies in the case of Kosovo not only theoretical but also practical aspects. The ideological misunderstanding of political parties in Kosovo at a first reading creates the idea of a virus that has passed in many countries with consolidated democracy. In this logic, we can not claim something different to us, for how long, the claim to refer to different doctrines is viewed with much scepticism. To achieve the objectives of the paper, we have elaborated the global effects that have in the ideologies of political parties in Kosovo. The paper found that Integration into the European Communities over the years has become an indisputable priority for any government in Kosovo. The integration process changes in the government program of any political force, not just on paper. It was observed there exists International organizations such as the IMF strive, with a degree of success, to push and impose aspects of globalization in a particular direction, and such discourses, such as neoliberal economic discourse, are an important part of the strategy for to achieve this goal. The findings, therefore, suggest that through participation in democratic elections, they want to represent these interests to representatives and formal political institutions.